Improving self-confidence and speaking skills in elementary students through action-based learning - Ardhian Zahroni; Mohammad Syaifuddin; Khozin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Low self-confidence and limited oral proficiency remain significant hurdles for young language learners, often exacerbated by high affective filters and conventional, non-interactive teaching methods. This study aims to evaluate the effectiveness of Action-Based Learning (ABL), integrated with gamified digital tools, in enhancing English-speaking skills and self-confidence among elementary school students. Drawing on constructivist learning theory and the Affective Filter Hypothesis, the pedagogical framework was operationalized through iterative